An atomistic simulation towards molecular design of silica polymorphs nanoparticles in polysulfone based mixed matrix membranes for CO2/CH4 gas separation - Lock, S.S.M. (John Wiley and Sons Inc, 2020)
Incorporation of inorganic fillers into Polysulfone (PSF) to constitute mixed matrix membranes (MMMs) has become a viable solution to prevail over limitations of the pristine materials in natural gas sweetening process. Nevertheless, preparation of MMMs without defects and empirical investigation of membrane that exhibits characteristic of improved CO2/CH4 separation performance at experimental scale are difficult that require prior knowledge on compatibility between the filler and polymer. A computational framework has been conducted to construct validated PSF based MMMs using silica (SiO2) as inorganic fillers. It is known that nanosized SiO2 can coexist in varying polymorph configurations (ie, Î±-Quartz, Î±-Cristobalite, Î±-Tridymite) but molecular simulation study of SiO2 polymorphs to form MMMs is limited. Therefore, this work is a pioneering study to elucidate feasibility in facile utilization of polymorphs to improve gas separation performance of MMMs. Physical properties and gas transport behavior of the simulated PSF based MMMs with different SiO2 polymorphs and loadings have been elucidated. The optimal MMM has been found to be PSF/25 wt Î±-Cristobalite at 55Â°C. The success in molecular simulation has shed light on how computational tools can provide understandings at molecular level to elucidate compatibility between varying pristine materials to MMMs for natural gas processing. Â© 2020 Society of Plastics Engineers